The Influence of Education Council Leadership and Policy on Solving Educational Problems in Wonosobo Regency, Indonesia - Haryanto, Sri (Yayasan Ilomata, 2024)
This study investigates the influence of leadership competence and the Board of Education policies on resolving educational issues in the Wonosobo Regency. A quantitative survey approach was used, involving 100 respondents consisting of educators and Board members. Data analysis was conducted using multiple linear regression in SPSS version 22. The descriptive results show that the Board’s competence scored an average of 70.79, while their policies averaged 65.55, indicating significant variability among respondents. Normality, multicollinearity, and heteroscedasticity tests confirmed that the data met the basic assumptions for regression. The regression analysis revealed that both the competence of the Board (t = 12.078, p < 0.001) and their policies (t = 7.762, p < 0.001) significantly impact the resolution of educational problems. The F-statistic of 7443.92 (p < 0.001) further confirmed the significance of the model. With an R-squared value of 0.693, the model explains 69.3% of the variability in solving educational problems. These findings suggest that improving leadership competence and policy effectiveness within the Board of Education is crucial to addressing educational challenges in the Wonosobo Regency. Consequently, the null hypothesis was rejected, and the alternative hypothesis was accepted, emphasizing the strategic role of the Board of Education in enhancing educational quality and effectiveness in the region.